User Experience Analysis of a Multimodal Digital Application Integrating Multiple Intelligences for Young Learner - Rini Juliana Sipahutar; Natalia Silalahi; Nina Afria Damayanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Despite the increasing adoption of multimodal educational applications for young learners, empirical research that explicitly examines young learner’s user experience from the perspective of cognitive diversity remains limited. Many existing studies emphasize learning outcomes or technical usability, while insufficient attention is given to affective engagement, interaction behavior, and experiential quality during young learner’s interaction with multimodal systems. This gap highlights the need for a structured analysis of how multimodal interaction grounded in the Multiple Intelligences (MI) framework shapes young learner’s user experience. This study examines young learner’s user experience while interacting with an existing multimodal educational application that incorporates the MI framework as a foundation for its interaction structure. The research explores how visual, auditory, and kinesthetic elements influence children’s engagement, affective responses, and interaction behaviors. A qualitative descriptive design was employed through systematic observation and semi-structured interviews involving five young learners aged 5–6 years (N = 5), along with accompanying educators. The study introduces an adapted user experience analysis framework tailored for young learner’s multimodal interaction contexts. Thematic analysis was conducted to identify interaction patterns and usability factors shaping the overall experience. The findings indicate that multimodal interaction enhances engagement, motivation, and accessibility, particularly for children with diverse intelligence profiles. Integrating Multiple Intelligences principles supports adaptive interaction pathways that improve satisfaction and sustained attention. This study contributes to the field of Human Computer Interaction (HCI) by providing empirical evidence on how cognitive diversity can inform the evaluation and design of multimodal interfaces for young learners.